2022
DOI: 10.3390/biomedicines10112976
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Head Rotations Result in Persistent Gait Alterations in Piglets

Abstract: Multiple/repeated mild traumatic brain injury (mTBI) in young children can cause long-term gait impairments and affect the developmental course of motor control. Using our swine model for mTBI in young children, our aim was to (i) establish a reference range (RR) for each parameter to validate injury and track recovery, and (ii) evaluate changes in gait patterns following a single and multiple (5×) sagittal rapid non-impact head rotation (RNR). Gait patterns were studied in four groups of 4-week-old Yorkshire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Auditory and visually evoked potentials were captured using methods published previously in healthy piglets [46,47] on each animal before head rotations, to establish a pre-injury baseline, and again at 1, 4, and 7 days after to examine the acute time-course of mild TBI on stimulus processing. Other neurofunctional measures were also collected using this experimental injury paradigm and include piglet gait and pupillary light reflexes, using previously published methods [48,49].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditory and visually evoked potentials were captured using methods published previously in healthy piglets [46,47] on each animal before head rotations, to establish a pre-injury baseline, and again at 1, 4, and 7 days after to examine the acute time-course of mild TBI on stimulus processing. Other neurofunctional measures were also collected using this experimental injury paradigm and include piglet gait and pupillary light reflexes, using previously published methods [48,49].…”
Section: Methodsmentioning
confidence: 99%
“…The 8 min interval between impacts for the repeated RNR group was determined from the same high-school soccer heading data, where girls and boys received 4 and 6 impacts per h, respectively, where impacts were spaced 8 min apart for both sexes. Further details on the determination of piglet head rotation magnitudes are described in [48]. EEG measurements were taken on a pre-injury day (D-1), one (D1), four (D4) and seven days (D7) post-injury (Figure 1).…”
Section: Rapid Non-impact Rotational Injury (Rnr)mentioning
confidence: 99%
“…These rats also experienced deficits in behavior, exhibited anxiety and increased corticosterone levels following rTBI ( 70 ). When piglets experienced one high-level rotational injury versus one high-level rotational injury with four subsequent mid-level rotational injuries administered 8 min apart, the multiple rotation injury group experienced greater gait times 1 day post after injury ( 71 ). Overall, gait patterns were normal in the single rotation group but were abnormal following the additional rotations ( 71 ), suggesting the long-term effect of repeated rotational brain injury on locomotor behavior.…”
Section: Mechanisms Of Acute and Repeated Traumatic Brain Injurymentioning
confidence: 99%
“…When piglets experienced one high-level rotational injury versus one high-level rotational injury with four subsequent mid-level rotational injuries administered 8 min apart, the multiple rotation injury group experienced greater gait times 1 day post after injury ( 71 ). Overall, gait patterns were normal in the single rotation group but were abnormal following the additional rotations ( 71 ), suggesting the long-term effect of repeated rotational brain injury on locomotor behavior. Recent studies underscored the accumulating nature of symptoms in adolescents with repeated concussions, with higher symptom scores observed after the second concussion compared to the initial one ( 72 ).…”
Section: Mechanisms Of Acute and Repeated Traumatic Brain Injurymentioning
confidence: 99%
“…Oeur et al applied single and repeated low-velocity head rotations in piglets and also gathered data from adolescent humans presenting with concussion, and found that deficits in the pupillary light reflex were altered after injury compared to reference ranges, suggesting that pupillometry could be a valuable tool for neurofunctional assessment [2]. Mull et al reported significant gait alterations in piglets following rotational acceleration that were more severe and longer lasting when multiple rotations were applied, and they also validated reference ranges for assessing gait alterations in piglets [3]. Dr. Oeur and colleagues also investigated auditory and visually evoked potentials following rotational acceleration in piglets, and found that single and repeated injury groups exhibited different alterations to their evoked potential responses [4].…”
mentioning
confidence: 95%